Perception and Social Image of the Nursing Profession: A Study from Pokhara, Kaski - Poudel, Shrijana; Baral, Binita (International Research Journal of MMC, 2025)
Nursing is unique profession focused on the care of individuals, families, and communities to attain, maintain or recover optimal health and quality of life. This study is designed to find out the public perception regarding nursing profession among people of Pokhara, Kaski. A descriptive cross-sectional research design was adopted for the study by using non-probability purposive sampling technique with 110 respondent of age group 40-59 years from Pokhara, Kaski. A structured face to face interview schedule with 5-point Likert scale was used to collect the data. Obtained Data were entered in SPSS and analyzed by using descriptive statistics for baseline information and perception. Inferential statistics method chi-square test was used to find the association between selected background information and perception on nursing profession. The finding of the study revealed that more than half 51.8% of the respondent had a positive perception and 48.2% had negative perception regarding nursing profession. There was statically significant association between level of perception and occupation (p value = <0.041) and educational status and level of perception (p value = <0.006). Hence, quality of nursing profession needs to be enhancing the positive perception among people through quality of nursing services.